Patient safety culture awareness among healthcare providers in a tertiary hospital in Riyadh, Saudi Arabia - Alsulami, Abdulkarim; A'aqoulah, Ashraf; Almutairi, Nouf (Frontiers in Public Health, 2022)
Patient safety is a serious concern in the health care industry. To enhance patient safety, healthcare providers are expected to minimize accidental harm to patients and enhance the quality of patient-centered care. The main objective of this study is to explore the awareness of the patient safety culture among healthcare providers. It is further intended to assess key fields and factors that hinder patient safety adoption and determine the effects of demographic factors on healthcare providers’ awareness of patient safety culture. This study applied a cross-sectional quantitative design. It was conducted in a tertiary hospital in Riyadh, Saudi Arabia. The participants consisted of all healthcare providers working in a specific tertiary hospital in Saudi Arabia. A random sampling technique was applied in this study. The study sample size was 409 participants. A valid and reliable questionnaire was used to collect the required data. The T-tests, ANOVA. And regression was used. The study found that there is a moderate level of patient safety culture awareness among healthcare providers. Moreover, the findings also revealed that the age group “31-40” showed statistically different awareness levels as compared to the "more than 50 years' age group" (p=.012). Also, this study has found that gender and education have a significant influence on the awareness level of patient safety culture while position and work area have no influence on the awareness level of patient safety culture among healthcare providers. Managers in healthcare institutions should develop speeder response plans and make them part of the patient safety culture. Institutions offering bachelor’s degrees and postgraduate in nursing should pay more attention to the subject of patient safety. The government healthcare sector, together with the private healthcare sector, should continuously train healthcare providers on patient safety procedures to improve the patient safety culture. Healthcare providers should be encouraged to report errors made during diagnosis or treatments to avoid them in the future.